Respiração de frutos e permeabilidade de filmes poliméricos - Steffens, Cristiano André (2006)
The objective of this work was to evaluate the respiration and respiratory quotient of fruits of several species with respect to cultivars, ripening stage, temperature and atmosphere conditions during storage, to obtain information about the possibility of fermentation and physiological disorders occurrence in fruits stored in modified atmosphere. Also, we aimed at developing a methodology to evaluate the permeability to O2 and CO2 of polymeric films under experimental storage conditions in order to provide results that could be used to choose film for storaging fruits in modified atmosphere. Respiration of fruits of some cultivars of apple, kiwifruit, persimmon and peach, in two ripening stages at harvest, different temperatures (0, 10 and 20ºC) and storage conditions (cold storage and modified atmosphere) were evaluated. The effect of storage conditions on the internal breakdown, alcoholic taste and the relation of these parameters with respiration in Jubileu peach and Bruno kiwi was evaluated. For the study of permeability of polymeric films, the effect of relative humidity, temperature (0, 5, 10, 15, and 20ºC) and concentration gradient of gases (10, 15, and 20% of O2 and 5, 10, and 15 of CO2) on the permeability of different polymeric films (cellophane permeable and inpermeable to water vapour, polyvinyl chloride, nylon, polypropylene bioriented, low and high density polyethylene) was evaluated. The effect of thickness, density, presence of additives, temperature and concentration gradient of gases on the permeability of polyethylene films was also determined. Internal breakdown incidence and presence of alcoholic taste in Jubileu peach and Bruno kiwi were lower at the lowest levels of CO2 (5 and 8kPa), independently of O2 level, respectively. The incidence of these physiological disorders, in both species, showed positive correlation with respiratory quotient and negative with respiration of fruits. Gala apple, stored at 0ºC, and Fuji apple, at 0 and 10ºC, did not show a characteristic of climacteric respiratory rise. Fruit ripening stage at harvest influenced the respiration rate at two apple cultivars and at Giombo persimmon at 0ºC and at Fuyu and Rama Forte persimmons stored at 10ºC. The respiration rate was influenced by cultivars in all species of evaluated fruits. The increase of temperature had a strong effect on the increment in respiration rate. Q10 value ranged according to species and with range of temperature. The modification of atmosphere, on average, reduced the respiration rate in 14.3%, at 0°C. The permeation chamber projected and constructed permitted to evaluate polymeric films in relation to gases permeability and its determination must be done under conditions like those used in commercial storage. Results of gases permeability, obtained by the methodology described could be used for choosing a suitable film to the store fruits in modified atmosphere.